Massive pericardial lipoma causing haemodynamic compromise in a neonate - T.G.M. Prasadani; A.S. Athapathu; S.A. Gunaratne; R.M.S. Perera (Elsevier, 2020)
Cardiac tumours are rare in neonates. Most are benign and have a favourable outcome. However they can cause significant morbidity and mortality secondary to cardiac compromise. We present the first reported case of pericardial lipoma in a neonate.A baby detected to have a cardiac tumour by foetal echocardiography was delivered at term. Even though initially stable, he developed cardiac arrest at 10 minutes of life, needing resuscitation, ventilation and inotropic support. A massive pericardial tumour measuring 4.5cm by 3.5cm with a pericardial effusion was diagnosed by 2D echocardiography and confirmed by non-contrast CT scan. It was excised on day one of life, however the baby succumbed during surgery due to severe left ventricular dysfunction while weaning off from cardio-pulmonary bypass.Lipomas constitute less than 5% of cardiac tumours in children. Knowledge on pericardial lipomas in children is limited to only a few case reports.Although histologically benign, pericardial tumours can cause cardiac compromise by outflow/inflow obstruction and cardiac tamponade. Management depends on degree of haemodynamic compromise.This case report presents the first reported pericardial lipoma in a neonate and highlights the fact that even histologically benign lipomas can cause significant morbidity and mortality depending on tumour size and location.